2020
DOI: 10.1038/s42003-020-01314-4
|View full text |Cite
|
Sign up to set email alerts
|

IM30 IDPs form a membrane-protective carpet upon super-complex disassembly

Abstract: Members of the phage shock protein A (PspA) family, including the inner membrane-associated protein of 30 kDa (IM30), are suggested to stabilize stressed cellular membranes. Furthermore, IM30 is essential in thylakoid membrane-containing chloroplasts and cyanobacteria, where it is involved in membrane biogenesis and/or remodeling. While it is well known that PspA and IM30 bind to membranes, the mechanism of membrane stabilization is still enigmatic. Here we report that ring-shaped IM30 super-complexes disassem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 76 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Although the physiological role of Vipp1 within the cell is not fully understood, the results of many cell biological studies indicate that this protein family functions to mitigate stress in photosynthetic membranes ( Bryan et al., 2014 ; Zhang and Sakamoto, 2015 ; Zhang et al., 2012 , 2016 ) as well as in thylakoid membrane biogenesis and repair ( Aseeva et al., 2007 ; Fuhrmann et al., 2009b ; Gao and Xu, 2009 ; Gutu et al., 2018 ; Kroll et al., 2001 ; Lo and Theg, 2012 ; Nordhues et al., 2012 ; Walter et al., 2015 ; Westphal et al., 2001 ; Zhang and Sakamoto, 2015 ). In addition, some studies have shown that Vipp1 can seal and repair leaky membranes in vitro ( Junglas et al., 2020 ; Siebenaller et al., 2020 ). Similarly, the closely related bacterial PspA is known to mediate inner membrane repair in response to stress ( Joly et al., 2010 ; Kobayashi et al., 2007 ; McDonald et al., 2015 , 2017 ), whereas the PspA homolog LiaH in Bacillus subtilis protects the cell against oxidative stress and cell wall-targeted antibiotics ( Wolf et al., 2010 ), and the homolog Rv2744c in Mycobacterium tuberculosis re-locates to the membrane surface of lipid droplets ( Datta et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological role of Vipp1 within the cell is not fully understood, the results of many cell biological studies indicate that this protein family functions to mitigate stress in photosynthetic membranes ( Bryan et al., 2014 ; Zhang and Sakamoto, 2015 ; Zhang et al., 2012 , 2016 ) as well as in thylakoid membrane biogenesis and repair ( Aseeva et al., 2007 ; Fuhrmann et al., 2009b ; Gao and Xu, 2009 ; Gutu et al., 2018 ; Kroll et al., 2001 ; Lo and Theg, 2012 ; Nordhues et al., 2012 ; Walter et al., 2015 ; Westphal et al., 2001 ; Zhang and Sakamoto, 2015 ). In addition, some studies have shown that Vipp1 can seal and repair leaky membranes in vitro ( Junglas et al., 2020 ; Siebenaller et al., 2020 ). Similarly, the closely related bacterial PspA is known to mediate inner membrane repair in response to stress ( Joly et al., 2010 ; Kobayashi et al., 2007 ; McDonald et al., 2015 , 2017 ), whereas the PspA homolog LiaH in Bacillus subtilis protects the cell against oxidative stress and cell wall-targeted antibiotics ( Wolf et al., 2010 ), and the homolog Rv2744c in Mycobacterium tuberculosis re-locates to the membrane surface of lipid droplets ( Datta et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, by tuning the CTD, spiral filaments can readily anneal to form planar crystalline concentric or linear sheets (Supplementary Figure 3D), which would stabilise damaged membrane acting as a physical barrier and supporting scaffold. Such structures explain how Vipp1 and other bacterial homologues such as PspA might inhibit proton leakage across membranes 46,58 . Finally, Vipp1 helical filaments may form membrane bridges linking thylakoids and the chloroplast envelope 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This filament is used to build different supramolecular structures including spirals 33,[35][36][37][38][39][40][41][42][43][44] , helical filaments 9,33,43,45 and dome-shaped rings 1,34 . In bacteria, although Synechocystis Vipp1 46 and PspA 9 form planar patches, spiral filaments have not been reported, which currently represents a key differentiating factor from their eukaryotic counterparts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane‐associated protein can also play a role in membrane remodelling. For example, the molecular mechanism by which the protomers of IM30 protein (for Inner Membrane protein of 30 kDa) self‐assemble to thylakoid membranes has been described using a range of biophysical technics such as atomic‐force spectroscopy, SAXS and modelling [114]. Their association with the thylakoids results in the formation of a protective carpet and their intrinsically disordered C‐terminal tail unfolds and promotes pore forming.…”
Section: Biosynthesis Of Thylakoid Lipids and Their Supramolecular As...mentioning
confidence: 99%